Low Prevalence of Pre-Treatment and Acquired Drug Resistance to Dolutegravir among Treatment Naïve Individuals Initiating on Tenofovir, Lamivudine and Dolutegravir in Zimbabwe - Vinie Kouamou; Tendai Washaya; Chiratidzo Ellen Ndhlovu; Justen Manasa (Viruses, 2023)
Dolutegravir (DTG) use in combination with tenofovir and lamivudine (TLD) is scaling up in Africa. However, HIV drug resistance (HIVDR) data to DTG remain scarce in Zimbabwe. We assessed the prevalence and genetic mechanisms of DTG resistance in people living with HIV initiating on TLD. A prospective cohort study was conducted between October 2021 and April 2023 among antiretroviral therapy (ART) naïve adults (≥18 years) attending care at an HIV clinic in Zimbabwe. Pre-treatment drug resistance (PDR) was assessed prior to TLD initiation and viral load (VL) outcome and acquired drug resistance (ADR) to TLD were described after 24 weeks follow-up. In total, 172 participants were enrolled in the study. The median (IQR) age and log10 VL were 39 (29–48) years and 5.41 (4.80–5.74) copies/mL, respectively. At baseline, no PDR to DTG was found. However, as previously reported, PDR to non-nucleotide reverse transcriptase inhibitor (NNRTI) was high (15%) whilst PDR to NRTI was low (4%). After a median duration of 27 (25–30) weeks on TLD, virological suppression (VL < 1000 copies/mL) was 98% and among the 2 participants with VL ≥ 1000 copies/mL, no ADR was found. HIVDR to DTG is rare among ART naïve individuals. DTG is more likely to address the problems of HIVDR in Africa.